A Survey on Italian General Practitioners’ Perspectives Regarding the Reorganization of Primary Care Services - Causio, Francesco Andrea; Gentili, Andrea; Beccia, Flavia; De Maio, Lucia; Melnyk, Andreiy; Quaranta, Gianluigi; Russo, Luigi; Savoia, Cosimo; Cascini, Fidelia (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. This study investigates the perspectives of primary care doctors in Italy regarding recent healthcare reforms, including the introduction of Community Hospitals and Community Homes.Methods. An online survey was conducted with 43 General Practitioners from various regions of Italy.Results. The results reveal diverse opinions on the potential benefits of Community Hospitals and Community Homes in enhancing primary care and reducing inappropriate emergency room visits. While some GPs expressed optimism, a substantial portion raised concerns about inadequate dissemination of information and lack of clarity regarding admission criteria and functions. The study also highlights disparities in digital literacy and utilization of electronic health records and telemedicine platforms among GPs. Conclusion. These findings suggest the need for improved communication, training, and support to ensure successful implementation of healthcare reforms and digital transformation in Italy’s primary care system.Highlights. Italian GPs express diverse opinions on the potential benefits of Community Hospitals and Community Health Houses in enhancing primary care.The study findings highlight the different perspectives and challenges faced by General Practitioners in Italy, regarding the reorganization of Primary Care Services and, in particular, the implementation of community hospitals, community health homes and digital healthcare initiatives.Disparities in digital literacy and utilization of electronic health records and telemedicine platforms among GPs highlight the need for targeted training and support programs.